Understanding the Relation between Printing and Material Parameters of Time-Pressure Dispensing System for Bioprinting - Lee, Jia Min (2016)
Bioprinting, a computer-aided printing, is an emerging field in tissue engineering. The ability to print biological models from scanned medical images allows customizability in printed construct. Identifying input printing factors that affects dimensions of printed biological construct is important as it enables control over geometry of structure. Biocompatible hydrogel is used in bioprinting to incorporate cells into printing process. In this experiment, a time-pressure dispensing system is used. This article investigatesdifferent factors such as pressure of system, nozzle inner diameter, moving speed, and viscoelastic material that define the dimensions of printed construct. It is identified printed hydrogel achieves finer resolution at higher concentration, faster moving speed, smaller nozzle inner diameter and lower pressure.